Review: Authentication of grass-fed meat and dairy products from cattle and sheep. (23rd April 2020) - Prache, S.; Martin, B.; Coppa, M.
Abstract : Meat and dairy products derived from grassland carry premium values and sensory and nutritional qualities that aroused much interest for authentication methods to guarantee grassland origin claims. This article reviews the current state of knowledge on the authentication of meat and dairy of grassland origin from food analysis in both cattle and sheep. A range of methods alone or combined, involving analysis of elemental or molecular constituents of food product and fingerprinting profiling combined with chemometrics, have been developed and proved useful to differentiate contrasted feeding regimes and authenticate grass-fed meat and dairy. Their robustness and discriminatory reliability in more complex feeding conditions, such as in the case of dietary switches or when grass only makes up part of the animal's diet, are under active investigation. Our review highlights the possibilities and limitations of these methods, the latter being chiefly posed by variations in the quantity, characteristics and composition of grassland feedstuffs consumed by animals, which are nevertheless inherent to grassland-based production systems, variations in animal responses within and across breeds, and difficulties in detecting the consumption of non-grass feedstuffs by the animal. It also highlights a number of issues for consideration, points of caution and caveats in applying these methods. Scientists agree that much of the research carried out so far has been a 'proof of concept' type and that efforts should be made in the future to develop more databases to help gain genericity and robustness.